Lightweight Expanded Clay Aggregate (LECA) as replacement materials for geotechnical application - Azhani, Zukri; Ramli, Nazir; Dayang Zulaika, Abang Hasbollah; Amir Hamzah, Mustapha (Elsevier Ltd, 2023)
Settlement is a common geotechnical problem occurs in soft soils. The replacement method is the easiest way to improve this problematic soil. This technique is carried out by removing the unwanted part of the soil and replacing it with a more suitable material or soil. This study focuses on using Lightweight Expanded Clay Aggregate (LECA) as a construction material to replace normal sand and aggregate in filling work. LECA is one of the best alternatives that can be used to improve soil properties because it is lightweight, strong and environmentally friendly. However, there are no specific guidelines for the LECA replacement in filling work. Therefore, this study was conducted to develop the construction procedures and LECA replacement requirements for geotechnical application in Malaysia. LECA aggregates have been used as a filling material to solve the settlement problem at Masjid At-Taqwa, Teluk Intan, Perak, Malaysia. LECA samples were collected from different location at different compaction levels for inspection of physical properties and quality of compaction examination. The level of compaction effort performed on LECA replacement represents by the number of passes. The relationship in compaction conditions related to LECA replacement is determined by two graphs namely LECA Compaction Effort and Targeted Compaction Level. The compaction quality of LECA aggregate filling work can be checked using Lightweight Deflectometer (LWD). The maximum desired density can be determined in advance. With reference to the LECA Compaction Effort plot established in this study, the number of passes that need to be performed during the placement work can be planned according to the desired compact density. Whereas, the compaction level, R% can be predicted based on the Target Compaction Level plot. An LWD test should then be carried out to ensure that the compacted density reaches the required level.